2020
DOI: 10.1155/2020/8986521
|View full text |Cite
|
Sign up to set email alerts
|

Igg-Dependent Hydrolysis of Myelin Basic Protein of Patients with Different Courses of Schizophrenia

Abstract: The level hydrolysis of myelin basic protein (MBP) by IgG in patients with schizophrenia was studied depending on the clinical features and course of the disease. The patients were grouped according to type of schizophrenia and type of disease course. We found that IgGs isolated and purified from sera of schizophrenia patients’ blood hydrolyses human MBP, and the level of this hydrolysis significantly exceeds that of healthy individuals. Detection of protease activity corresponding only to intact IgGs in polya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 70 publications
1
19
1
Order By: Relevance
“…25 One study demonstrated that the increased activity of MBPhydrolyzing antibodies is caused by the activation of humoral immunity in schizophrenia. 26 In the present study, the levels of serum IL-1b, IL-6, and MBP were lower in the control group than in the type I and II patient groups. Previous studies have also reported that the levels of serum IL-1b and IL-6 are higher in patients with schizophrenia than in healthy individuals.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…25 One study demonstrated that the increased activity of MBPhydrolyzing antibodies is caused by the activation of humoral immunity in schizophrenia. 26 In the present study, the levels of serum IL-1b, IL-6, and MBP were lower in the control group than in the type I and II patient groups. Previous studies have also reported that the levels of serum IL-1b and IL-6 are higher in patients with schizophrenia than in healthy individuals.…”
Section: Discussioncontrasting
confidence: 45%
“… 25 One study demonstrated that the increased activity of MBP-hydrolyzing antibodies is caused by the activation of humoral immunity in schizophrenia. 26 …”
Section: Discussionmentioning
confidence: 99%
“…Catalytic antibodies are only a minor part of natural antibodies but significantly enhance the immune system’s functionality ( 55 ). Catalytic antibodies hydrolyzing DNA ( 56 ), RNA and miRNA ( 57 , 58 ), histones ( 59 ), and myelin basic protein (MBP) ( 60 , 61 ) have been described in schizophrenia. Notably, these antigens are DAMPs.…”
Section: Alterations In the Innate Immune System In Schizophreniamentioning
confidence: 99%
“…Antibodies hydrolyzing myelin basic protein have been found and described in detail in multiple sclerosis (MS) [34], systemic lupus erythematosus (SLE) [35], autism [36], and schizophrenia [37]. We also showed earlier pronounced differences in the level of MBP-hydrolyzing activity of serum antibodies depending on the clinical features of schizophrenia, such as the type of course of the disease, the duration of the disease, and the presence of remission [38]. In addition, the cross-reactivity of antibodies with histone-hydrolyzing and MBP-hydrolyzing activity, as shown in a series of studies [39][40][41][42], indicates a connection between inflammation and damage of the myelin sheath.…”
Section: Introductionmentioning
confidence: 59%